(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study investigated the effect of graphical organizer and metacognitive reading on Junior secondary school two (JSS2) students’ academic achievement in algebra in Onitsha Education Zone of Anambra State. One research question guided the study and one null hypothesis were tested at 0.05 alpha level A quasi experimental research design, specifically, pre-test, post-test non-equivalent control design was used. The population of the study consists of 4,433 JSS2 students while 150 students formed the sample size. The sample technique employed was multistage sampling. The research instrument used for data collection was the mathematics achievement test. The instrument was validated by three experts and Kuder Richardson Formula 20 was used to ascertain the reliability coefficient at 0.87. Mean, standard deviation and analysis of covariance were used for data analysis. The findings of the study showed that students taught algebra using Graphic Organizer and metacognitive reading strategies significantly achieved more than those taught with traditional method and students taught algebra using graphic organizer achieved significantly higher than those taught using conventional method of teaching. It was recommended among others that in-serving mathematics teachers should be trained by government and ministry of education on the use of graphic organizer and metacognitive reading strategies through workshops, seminars.